2017
DOI: 10.1049/el.2017.2689
|View full text |Cite
|
Sign up to set email alerts
|

DBR‐free semiconductor disc laser on SiC heatspreader emitting 10.1 W at 1007 nm

Abstract: We report a distributed Bragg reflector-free semiconductor disc laser which emits 10 W continuous wave output power at a wavelength of 1007 nm when pumped with 40 W at 808 nm, focused into a 230 μm diameter spot on the gain chip. By introducing a birefringent filter plate in the laser cavity the wavelength could be tuned from 995 to 1020 nm. The laser consisted of a gain chip located at the beam waist of a linear concentric resonator with an output coupling of 2.15%. The gain chip consists of a 1.574-μm-thick … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 10 publications
1
17
0
Order By: Relevance
“…As it can be seen in Fig. 2, these advantages are remarkable and have pointed out to the possibility of using more affordable heat spreaders with lower thermal conductivity, such as SiC [8], [9], yet enabling power scaling to watt-levels [10], [11].…”
Section: Introductionmentioning
confidence: 96%
“…As it can be seen in Fig. 2, these advantages are remarkable and have pointed out to the possibility of using more affordable heat spreaders with lower thermal conductivity, such as SiC [8], [9], yet enabling power scaling to watt-levels [10], [11].…”
Section: Introductionmentioning
confidence: 96%
“…For lasing wavelengths near 1 µm, the single heatspreader geometry has demonstrated an output power of 6 W when directly bonded to diamond [8]. Recently, using a single SiC heatspreader, Mirkhanov et al [9] reported 6 W of output power at a coolant temperature of 12°C, and 10.1 W at −10°C, while dual-diamond-heatspreader DBR-free SDLs have yielded 3.5 W, thus far limited solely by the available pump power [10]. In this paper, we directly compare the laser performance of DBR-free SDLs using these two geometries.…”
mentioning
confidence: 99%
“…The membrane is grown on a GaAs substrate, and between the substrate and the first capping layer is 200 nm of AlAs which acts as an etch stop. The sample is the same geometry as the one used in [17]. In preparing the membrane laser sample, the QW side of a sample chip is adhered to a piece of silicon wafer.…”
Section: Sample Description Imaging System and Calibrationmentioning
confidence: 99%
“…MQWLs exhibit a number of advantages, some of which are similar to other epitaxially grown semiconductor membranes [15,16,17,18]: (i) the thin growth with released stresses exhibits excellent crystallinity, and hence reduced non-saturable losses; (ii) MQWLs can be grown in about a tenth of the time that is needed to grow a VECSEL or polariton laser, and therefore are an ideal platform to investigate new functionalities; (iii) MQWLs are an ideal geometry in order to extract heat by contact bonding to sapphire or SiC, and can therefore be highly efficient lasers; (iv) MQWL growth is freed from the material (lattice matching) constraints of DBR mirror growth, which can adversely affect the quality of growth (a typically observed characteristic of VECSELs and some polariton lasers); and therefore (v) MQWLs can be designed in a wider selection of design wavelengths as the lack of DBR liberates the development of lasers at wavelengths where appropriate DBR material index contrast is not possible, such as the all-important 1.5 µm telecoms wavelength region; and finally, (vi) because of the high index contrast between the membrane material system and the substrate (silicon carbide, silica etc. ), strong waveguiding is formed which ensures a high overlap of the guided mode with the QW gain region.…”
Section: Introductionmentioning
confidence: 99%